SOUTH AFRICAN DAIRY INDUSTRY AND THE USE OF INTERCULTURAL BUSINESS COMMUNICATION FOR IMPROVEMENT - Adanlawo, Eyitayo Francis; Vezi-Magigaba, Makhosazana Faith (International Journal of Innovative Technologies in Social Science, 2023)
The dairy industry is an important part of the highly diverse agricultural sector of South African economy. The industry is a significant contributor to the food security and it also provides many social and economic attributes to the nation. South Africa has the potential to be self-sufficient in milk production, the country currently imports fluid milk and processed dairy products. For the industry to attain a larger world market share, it has to be competitive. A proper and constant intercultural business communication (IBC) with nations that are advanced in the production of milk and dairy products is the key to improving the sector's competitiveness. In this regard, the study examines the role of innovative intercultural business communication for the improvement of South African dairy industry. A systematic review method was adopted for collection and analysis of data relevant to the study. Communication accommodation theory (CAT) was used to explain the  role  that communication plays in building relationship that will lead to improved production. The study revealed that intercultural business communication has the capacity to build relationships that will lead to improved production for dairy industries. The study recommends regular visitations to more advanced nations’ dairy farms and adequate training on language and culture. Based on the conclusion and recommendations, this study presents a platform for the dairy industries to think about an innovative intercultural business communication approach to be at a competitive edge in a global environment.